The Influence of Information Technology and SCM on Competitive Advantage to Improve MSMEs Performance - Andri Ikhwana; Sasi Dianti (Institut Teknologi Bisnis AAS Indonesia, 2022)
The increasing number of MSMEs has a role for the national and regional economies. However, this increasing has not totally been released from the obstacles obstructing business development, especially in Garut Regency. Lack of capital, high raw materials, and difficulty in marketing products are some of the obstacles faced by business actors in Garut Regency. Meanwhile, based on the results of the regional competitiveness index report in 2019, it is known that Garut Regency falls into the moderate category and business dynamics are the pillars with the lowest conditions. The contribution of MSMEs and the increasing number of business competition as well as the condition of MSMEs of Garut Regency is currently the reason that MSMEs deserve attention. This research aims to explain the interactions occurring between variables in this study by testing the influence of information technology and SCM on competitive advantage to improve organizational performance in MSMEs in Garut Regency. Data on this study was obtained from 109 MSME actors in Garut Regency through the results of the spread questionnaires. While the technique used to analyse the data is Pearson product-moment correlation analysis and regression using SPSS statistics. This research reveals that: 1) Information technology influences supply chain management, 2) Information technology influences competitive advantage, 3) Information technology influences competitive advantage, and 4) Competitive advantage influences organizational performance.